Potentiating the germination kinetics and physiological vigour via microbial coating: A strategy for enhancing post-storage viability and shelf-life in green gram seed (Vigna radiata (L.) Wilczek) - Samrat Rej; Radha Prasanna; Sandeep Kumar Lal; Sudipta Basu; Priya Ranjan Kumar; Anjali Anand; Aditi Tayade (Journal of Stored Products Research, 2026)

Cyanobacteria-coated seeds for improved productivity and seed storability in direct-seeded and transplanted rice - Shreya Kumari; Aditi Tayade; Deepti Varsha; Yashbir Singh Shivay; Sudipta Basu; Sandeep Kumar Lal; Arun Kumar; Preeti Soni; Radha Prasanna (Cereal Research Communications, 2026)

Beneficial cyanobacteria as seed coatings to enhance the storability and viability indices of spinach seeds - Ravi Mourthy Nivedha; Radha Prasanna; Mujtahida Khatun; Deepti Varsha; Akanksha Bhardwaj; Sandeep Kumar Lal; Sudipta Basu; Samrat Rej; Awani Kumar Singh; Yashbir Singh Shivay (Biocatalysis and Agricultural Biotechnology, 2025)

Cyanobacteria-based nutrimental strategy to enhance yield and quality of spinach - Ravi Mourthy Nivedha; Radha Prasanna; Akanksha Bhardwaj; Nallappa Reddy Bavana; Shalini Gaur Rudra; Awani Kumar Singh; Sandeep Kumar Lal; Sudipta Basu; Yashbir Singh Shivay (Journal of Applied Phycology, 2024)

Developing microbial seed coating for enhancing seed vigour and prolonging storability in chickpea - Mujtahida Khatun; Radha Prasanna; Akanksha Bhardwaj; Sayan Makur; Sandeep Kumar Lal; Sudipta Basu; Priya Ranjan Kumar (South African Journal of Botany, 2024)

Aberrant glycosylation of secretory mucin from the oral cavity in tobacco consumers: a pilot study - Ravneet K Grewal; Priyanka Basu; Sandeep Kaur; Akshdeep Singh (Glycoconjugate Journal, 2024)

Efficacy of nanoparticles against purple blotch (Alternaria porri) of onion - G. Chaithanya; Atul Kumar; D. Vijay; Praveen Kumar Singh; Zakir Hussain; Sudipta Basu; Sandeep Kumar Lal (Indian Phytopathology, 2023)

Patient Understanding of Chemotherapy and Goals of Care as Provided by Different Care Team Members - Shanzay Suhail; Sandeep Basu; Sameer A. Batoo; Eyad S. Al-Hattab; Ola Kanj Ahmed; Barbara J. Eidahl; Scott H. Okuno (Journal of Cancer Education, 2023)
Chemotherapy can be challenging and overwhelming for patients, but when patients are knowledgeable about chemotherapy, their comfort level, overall satisfaction, and coping improve. It is currently unknown whether patients prefer information about chemotherapy to be provided by specific care team members and whether demographic characteristics affect learning preferences. We developed a 31-question questionnaire that asked patients when chemotherapy information was discussed and who they wanted that information to come from. The questionnaire was given to 50 patients who had completed 1 cycle of chemotherapy. Patients were evenly distributed among age categories of 45 to 64 years, 65 to 74 years, and 75 years or older. Thirty participants (60%) were women, 33 (66%) had high school degrees, and 23 (46%) were receiving their first chemotherapy regimen. Sixty percent of patients best understood goals of care from oncologists, 70% wanted goals of care to come from oncologists, and 61% best understood and wanted to understand logistics of chemotherapy from oncologists. Sixty-six percent of patients understood adverse effects when they were explained by nursing staff, and 56% wanted explanations of adverse effects to come from nursing staff. Patients did not prefer a specific care team member or information source when receiving financial cost information. Patients often preferred to receive chemotherapy information from their oncologist; however, other members of the care team also provided information to patients in a way that was understood.

Multifaceted genome-wide study identifies novel regulatory loci in SLC22A11 and ZNF45 for body mass index in Indians - Anil K. Giri; Gauri Prasad; Khushdeep Bandesh; Vaisak Parekatt; Anubha Mahajan; Priyanka Banerjee; Yasmeen Kauser; Shraddha Chakraborty; Donaka Rajashekar; Abhay Sharma; Sandeep Kumar Mathur; Analabha Basu; et al. (Molecular Genetics and Genomics, 2020)

Syntrophic association and performance of Clostridium, Desulfovibrio, Aeromonas and Tetrathiobacter as anodic biocatalysts for bioelectricity generation in dual chamber microbial fuel cell - Smita S. Kumar; Sandeep K. Malyan; Suddhasatwa Basu; Narsi R Bishnoi (Environmental Science and Pollution Research, 2017)